The relationship between macroeconomic variables and inflation in Malaysia / Norhazatul Ain Mohd Yusof - Mohd Yusof, Norhazatul Ain (Faculty of Business Management, 2014)
This paper aims at finding out the relationship between macroeconomic variables and inflation in Malaysia. The variables considered are inflation rate, money supply, gross domestic product, gross national expenditure, import of goods and service and interest rate. The sample of this study comprises each of the dependent and independent variables on yearly basis from 1984 to 2013. Methodology used for this study is by using Multiple Linear Regression with the time series data sourced from World Bank and The Global Economy. Thereafter, econometric tests are to be conducted to observe the relationship of macroeconomic variables to the inflation in Malaysia. Interactive software package E-view would be used for testing and analyzing the data collected. The study is an attempt to investigate the relationship of chosen macroeconomic variables towards inflation in Malaysia. Findings from previous research papers mostly on developed market indicate that macroeconomic variables do play significant role in the determination of inflation. The result of this research paper would provide us with an indicative view and could form an important basic for policy makers to promote economic growth.